Guideline adherence for the surgical treatment of T1 renal tumours correlates with hospital volume: an analysis from the British Association of Urological Surgeons Nephrectomy Audit. (18th August 2019) - Tran, Maxine G.B.; Aben, Katja K.H.; Werkhoven, Erik; Neves, Joana B.; Fowler, Sarah; Sullivan, Mark; Stewart, Grant D.; Challacombe, Ben; Mahrous, Ahmed; Patki, Prasad; Mumtaz, Faiz; Barod, Ravi; et al.
Abstract : Objective: To assess European Association of Urology guideline adherence on the surgical management of patients with T1 renal tumours and the effects of centralisation of care. Patients and methods: Retrospective data from all kidney tumours that underwent radical nephrectomy (RN) or partial nephrectomy (PN) in the period 2012–2016 from the British Association of Urological Surgeons Nephrectomy Audit were retrieved and analysed. We assessed total surgical hospital volume (HV; RN and PN performed) per centre, PN rates, complication rates, and completeness of data. Descriptive analyses were performed, and confidence intervals were used to illustrate the association between hospital volume and proportion of PN. Chi‐ squared and Cochran–Armitage trend tests were used to evaluate differences and trends. Results: In total, 13 045 surgically treated T1 tumours were included in the analyses. Over time, there was an increase in PN use (39.7% in 2012 to 44.9% in 2016). Registration of the Preoperative Aspects and Dimensions Used for an Anatomical (PADUA) complexity score was included in March 2016 and documented in 39% of cases. Missing information on postoperative complications appeared constant over the years (8.5–9%). A clear association was found between annual HV and the proportion of T1 tumours treated with PN rather than RN (from 18.1% in centres performing <25 cases/year [lowest volume] to 61.8% in centres performing ≥100 cases/year [high volume]), which persisted after adjustment for PADUA complexity. Overall and major (Clavien–Dindo grade ≥III) complication rate decreased with increasing HV (from 12.2% and 2.9% in low‐volume centres to 10.7% and 2.2% in high‐volume centres, respectively), for all patients including those treated with PN. Conclusion: Closer guideline adherence was exhibited by higher surgical volume centres. Treatment of T1 tumours using PN increased with increasing HV, and was accompanied by an inverse association of HV with complication rate. These results support the centralisation of kidney cancer specialist cancer surgical services to improve patient outcomes.